Entrepreneurship and Liquidity Constraints: Evidence from Sweden - Jenny Nykvist (Uppsala University, Department of Economics, 2005)
Do potential entrepreneurs face liquidity constraints? Or to put it differently, does a person have to be wealthy to start a new business? This question has been discussed in a large literature that has documented a positive relationship between initial wealth and entrepreneurship. However, in a recent paper Hurst and Lusardi (2004) use higher order of polynomials in wealth and find that there is no relationship between household initial wealth and the probability of starting an own business throughout most of the wealth distribution in the United States. In this paper we examine this relationship using similar methods on Swedish data. The data set used is LINDA, a register-based longitudinal data set for Sweden. The relationship is estimated using probit models with different specifications of wealth. However, the result that wealth is not important for new entrepreneurs cannot be replicated. Instead, the main finding of the paper is that the relationship between wealth and transition into entrepreneurship is positive but diminishing for the major part of the wealth distribution. Moreover, the relationship between wealth and entrepreneurship gets stronger as the models get less restricted with respect to wealth. Our result leads us to the conclusion that liquidity constraints do play a significant role when determining transition into entrepreneurship in Sweden.
urn:nbn:se:uu:diva-79353
Keywords: D31; J23; J24; M13; 330; Liquidity constraints; wealth; entrepreneurship; starting capital; business ownership; Unternehmensgründung; Entrepreneurship-Ansatz; Vermögen; Schätzung; Schweden